Effect of Supervision and Monitoring of Teachers on Academic Performance in Public Secondary Schools in Marani Sub County, Kenya - Mweruti Samwel,; Dr. Joshua Odhiambo Ogal, (IJRDO- Journal of Educational Research, 2020)
Absenteeism of teachers is a key challenge for the human relations in the business world especially in schools. Many instructors fail to attend their lessons on any specific school day in the world. Absenteeism of teachers is a long-term challenge internationally and is worst in developing nations than the developed ones. The purpose of this study was to find out the effect of teachers’ absenteeism on form four students’ performance in public secondary schools in Marani Sub County, Kenya. The theory that guided the current study is the cultural theory by Christopher Hood, which describes how the managers of public institutions can reform the organizations for better performance through the continuous monitoring of their workers. The study used descriptive survey design and a sample of 10 Principals and 90 teachers in Marani Sub-County. Simple random sampling technique was used to choose the teachers while purposive sampling technique was used to choose the principals who formed the respondents of the study. Data was collected through the use of a questionnaire and interview schedules, and analyzed using descriptive and inferential statistics respectively. The findings of this study were useful to the government and school principals as it found the main reasons for the absenteeism of instructors, which would help to adjust the teachers’ conduct towards the performance of their work. The study also produced useful information to the parents concerning the performance of form four students in public secondary schools. The study established those teachers’ absenteeism results in low performance of form four students in public secondary schools. The study recommends that teachers should be monitored and disciplinary action taken against the teachers who are absent from school in order to reduce the rate of absenteeism. The Teachers Service Commission should continue promoting the instructors who have experience of teaching to help improve the performance of form four students in secondary schools.